Hubungan Antara Luas Daerah Tangkapan Terhadap Angka Koreksi Hidrograf Satuan Sintetik Gama 1 : The Relationship Between Catchment Area Size And The Gamma 1 Synthetic Unit Hydrograph Correction Factor - Widyasari, Titiek; Achmad, Nizar; Bhakty, Tania Edna; Gista, Felicita Erma (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The principle of the unit hydrograph (HS) method is the direct runoff hydrograph due to effective rainfall, which remains at 1 mm/hour and is uniform across the entire catchment or river basin area, thus requiring verification for the use of the HS method and examining the relationship between catchment area and correction factor. This research uses the HSS Gama 1. The parameters investigated for HSS Gamma 1 are parameters in four catchment areas in Yogyakarta, namely DAS Progo, Sub-DAS Winongo, Sub-DAS Code, and Sub-DAS Ngrancah. The results of this study indicate that the larger the catchment area, the smaller the thickness of rainfall on HSS Gama 1. If the thickness of rainfall is less than 1 mm/hour, then hydrograph the HSS Gama 1 of correction below hydrograph the HSS Gama 1 of initial. There is a correlation between the catchment area and the correction factor, meaning that the larger the catchment area, the greater the correction factor in the HSS Gama 1 method with the logarithmic regression method and a correlation coefficient of 0.9958.